Actinomycotic lacrimal canaliculitis: a rare case report - Bashir, Humaira; Nazir, Asifa (International Journal of Advances in Medicine, 2019)
Actinomyces israelii is a gram-positive anaerobic organism commonly associated with canaliculitis in adults. Actinomyces are normal commensal bacteria in humans and primarily cause opportunistic infections during immunosuppressive state or when loss of continuity of epithelial lining in mucosa occurs. Lacrimal canaliculitis is a relatively rare condition and is undiagnosed for long periods of time. Being a relatively rare condition, it is commonly overlooked and undiagnosed for long periods of time. Primary chronic canaliculitis is an uncommon problem and Actinomycosis may form in up to 2% of all lacrimal disease. Here present study reports a case of lacrimal canaliculitis caused by Actinomyces israelii.